Comparison of the efficacy based on clinicopathological characteristics and the safety of first-line treatments for patients with advanced ALK rearrangement non-small cell lung cancer: a network meta-analysis - Li, Yanwei; Wen, Yunxin; Zhang, Wenjing; Zhao, Yurong; Zhou, Ligui; Zeng, Xianrong; Kang, Xuefeng; Li, Luzhen (Frontiers in Oncology, 2026)
BackgroundDespite multiple phase III randomized controlled trials (RCTs) establishing first-line treatments for advanced anaplastic lymphoma kinase (ALK) rearrangement non-small cell lung cancer (NSCLC), the optimal regimen for diverse clinicopathological features remains unclear.MethodsPubMed, Embase, Cochrane Library, and ClinicalTrials.gov were searched for RCTs. The results of progression-free survival (PFS), overall survival (OS), objective response rate (ORR), grade 3–4 adverse events (AEs), and System Organ Class (SOC)-specific AEs (including hepatic, hematological, and gastrointestinal AEs) were compared and ranked, using network meta-analysis (NMA) and the surface under the cumulative ranking curve (SUCRA), with PFS considering various clinicopathological characteristics.ResultsA total of 3040 participants from 11 RCTs were enrolled, with data encompassing 10 distinct therapeutic regimens. In the overall patient cohort, lorlatinib achieved the longest PFS (93.9%) and the highest ORR (70.1%), whereas alectinib administered at a dose of 600 mg twice daily (bid) conferred the most favorable OS (83.7%) and the lowest incidence of grade 3–4 AEs (87.1%). The PFS efficacy profiles of the 10 regimens exhibited significant heterogeneity stratified by clinicopathological characteristics. Specifically, lorlatinib demonstrated superior efficacy in the Non-Asian subgroup (86.8%), patients without brain metastasis (84.7%), those with Eastern Cooperative Oncology Group performance status (ECOG PS) 0/1 (78.5%), males (71.2%), females (83.9%), patients aged < 65 years (74.3%), and never-smoking patients (89.7%). Alectinib (300 mg bid) demonstrated the optimal efficacy in the subgroups of brain metastasis (83.2%) and smoking history (90%), while alectinib (600 mg bid) ranked first in the subgroups of age ≥ 65 years (73%) and ECOG PS 2 (69.3%). Ensartinib achieved the optimal PFS in the Asian subgroup (71.8%). With respect to SOC-specific AEs, alectinib (300 mg bid) was associated with the lowest risk of hepatic AEs (87%) but carried the highest risk of anemia (11.3%). Iruplinalkib showed the lowest incidence of hematological AEs (72.2%), and alectinib (600 mg bid) had the lowest risk of gastrointestinal AEs (78.6%).ConclusionsLorlatinib demonstrated PFS advantage for advanced ALK rearrangement NSCLC, but OS benefit remains unestablished. Alectinib had the lowest hepatic and gastrointestinal AEs risk, while iruplinalkib had the lowest hematological AEs risk.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42023495527.